INTEGRATING THE SDGS INTO BRAZIL’S PUBLIC BUDGET: PATHWAYS FOR SUSTAINABLE GOVERNANCE TOWARD COP30 - GODINHO, PEDRO DE MORAIS; Vaz de Lima, Diana (RP3 - Revista de Pesquisa em Políticas Públicas, 2025)
Abstract This article examines Brazil’s recent efforts to integrate the Sustainable Development Goals (SDGs) into its federal planning and budgetary systems, with emphasis on the 2024–2027 Multi-Year Plan (PPA). Through qualitative and exploratory documentary analysis, it assesses the methodological design adopted to associate government programs with the SDGs, identifying advances, limitations, and opportunities for improvement. The study argues that the PPA represents an important innovation in policy coherence but remains limited in its translation to the Budget Guidelines Law (LDO) and the Annual Budget Law (LOA), where resource allocation and execution occur. As contextual evidence, the article also notes Brazil’s broader convergence with international sustainability standards, such as the national adaptation of IFRS S1 and S2 principles through NBC TDS 01 and 02, reflecting institutional alignment with global governance trends. By linking the discussion to the emerging agenda of climate finance and the Brazilian Emissions Trading System (SBCE), the paper highlights how sustainable budgeting can interact with mechanisms of carbon pricing and fiscal transparency. The findings point to methodological gaps in traceability, quantification, and standardization, and propose a unified coding model to enhance monitoring and accountability within Brazil’s federal budget, an essential step as the country prepares to host COP30 and strengthen its leadership in sustainable fiscal governance.